Improving the Quality and Productivity of the Higher Education Sector : Policy and Strategy for Systems-Level Deployment of Learning Analytics. - Siemens, George; Dawson, Shane; Lynch, Grace (Office for Learning and Teaching, 2013)
The report titled Improving the quality and productivity of the higher education sector: policy and strategy for systems-level deployment of learning analytics was commissioned by the Office for Learning and Teaching to promote discussion about the benefits of learning analytics and offers enabling suggestions for guiding future discussion around a coordinated national learning analytics agenda for Australia. Case studies illustrate how universities from around the world have used analytics to improve learning and teaching. The Society for Learning Analytics Research (SoLAR)2 is a not-for-profit organisation of leading international researchers exploring the impact of big data and analytics on the education sector.